EFFECT OF TEMPERATURE ON PHOTOELECTRIC PARAMETERS OF THREE-WAY ILLUMINATED SOLAR CELLS - Mirzaalimov, Avazbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract Objective. Increasing the efficiency of solar cells and reducing the amount of material used in its production is one of the important tasks of today. Methods. A 3-way sensitive solar cell was designed for this purpose. Compared with one surface, the efficiency of three surfaces increased by 2,81 times and two surfaces by 1,72 times. One of the main parameters of the environment is temperature. The daily temperature changes according to the seasons. Therefore, it is important to study the effect of temperature on solar elements. Results. In this scientific work, the effect of temperature on the photoelectric parameters of a three-way sensitive silicon-based solar cell was studied. It was found that the temperature coefficients of the photoelectric parameters of the three-way sensitive solar cell do not change when different areas are illuminated. Conclusion. It was determined that the temperature coefficient of the operating voltage is 2,52×10-3 V/K, and the temperature coefficient of the filling factor is 1,8×10-3 K-1. In addition, when the temperature changed from 300K to 350K, the short-circuit current in the three-side light state decreased by 4%.